2021
DOI: 10.3390/separations8040052
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Adsorption Capacities of Fungicides Using Peanut Shell Biochar via Successive Chemical Modification with KMnO4 and KOH

Abstract: This study explored the effects of peanut shell biochar (PSB) on the adsorption capacities of fungicides with and without successive chemical modifications, using KMnO4 and KOH (PSBOX-A), in order to provide a valuable understanding of their adsorption mechanisms and behaviors. To this end, the physicochemical properties of PSB and PSBOX-A were examined by using the Brunauer–Emmett–Teller method, Fourier transform infrared spectroscopy, and scanning electron microscopy with an energy dispersive X-ray spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In a special case, dewatered sludge samples with high content of iron-present as Fe 3 O 4 were revealed to have an advantage with persulfate activation leading to increase in oxygen radicals and porous properties which enabled removal of an azo dye [78]. Potassium permanganate is usually used along with other chemicals such as iron (Fe II) or potassium hydroxide producing chars with good properties [79][80][81]. Furthermore, there are also some other less studied methods of oxidation like electrochemical, graphite, and plasma treatments [74].…”
Section: Oxidation Activationmentioning
confidence: 99%
“…In a special case, dewatered sludge samples with high content of iron-present as Fe 3 O 4 were revealed to have an advantage with persulfate activation leading to increase in oxygen radicals and porous properties which enabled removal of an azo dye [78]. Potassium permanganate is usually used along with other chemicals such as iron (Fe II) or potassium hydroxide producing chars with good properties [79][80][81]. Furthermore, there are also some other less studied methods of oxidation like electrochemical, graphite, and plasma treatments [74].…”
Section: Oxidation Activationmentioning
confidence: 99%
“…In order to enhance the adsorption performance of biochar, researchers often use surface modification methods to improve the pore structure and the surface functional groups, such as chemical oxidation, chemical reduction, and metal impregnation [37,38]. Ferric chloride (FeCl 3 ) is a common chemical reagent that can provide hydrogen ions in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Pesticides are commonly used to enhance crop production and prevent plant diseases, such as fungal infections [1]. The United States Environmental Protection Agency reported that the global application of pesticides totaled more than 2 million tons and over USD 39 billion in 2007 [2].…”
Section: Introductionmentioning
confidence: 99%